STRUCTURAL DESIGN AND MOTION SIMULATION RESEARCH ON A NEW TYPE COMPOSITE ROTARY PERCUSSION DRILLING TOOL - ZHANG HaiPing; LIU XiaoDan; WANG JiaChang; SUN MingGuang (Jixie qiangdu)
A new type composite rotary percussion drilling tool was designed by studying the conversion mechanism of rotary to reciprocating motion. High-frequency axial impact and vibration was generated by an impact and energy transfer mechanism consisting of a couple of mating cams. A new kind of high rock breaking efficiency method was provided by combining the high speed rotation of positive displacement motor（ PMD） with the high-frequency impact of impactor. Detailed structural design and working principle analysis was carried out on impact and energy transfer mechanism,righting and falling and abrasion proof mechanism,power and binding mechanism,using software Creo Parametric 2. 0. Three dimensional solid modeling and the whole assembly of impact and energy transfer mechanism was completed. Motion simulation and indoor principle verification test were carried through. Results show that rotary power can be transferred into followers’ reciprocating impact by the impact and energy transfer mechanism,and that the tool ’s working principle is feasible,and it has simple structure and a good application prospect.